Визначення інформації, що містить пропаганду жорстокості: кримінально-правовий та кримінологічний аспекти - Олішевський, О. В.; Olishevskyi, O. V.; ORCID: http://orcid.org/0000-0003-1102-0675 (Вісник Кримінологічної асоціації України. - 2015. - № 2 (10). - С. 134-144., 2015)
Проаналізовано поняття «жорстокість» у семантичному, кримінально-правовому та кримінологічному аспектах. Визначено, які саме відомості або дані належать до інформації, що містить пропаганду жорстокості.

The concept of cruelty is needed to be improved. The issue of determining information or data should be related to the information containing propaganda of violence still remains not thoroughly studied. The studies of problems related to the cruelty were the interest of a number of domestic and foreign scientists. The authors provided their own definitions of cruelty and brutality, but they did not reveal what information or data should be related to the information containing propaganda of violence. The objective of this article is an attempt to analyze the category “cruelty” to improve its understanding in criminological, criminal and legal aspects. To determine what information or data should be related to the information containing propaganda of violence. Developers of international and legal agreements and participants of the European Court on Human Rights actively use the term “abuse”, defining its specific forms and manifestations, but a unified definition at this level has not been made. The national legislation has the similar situation. The Criminal Code of Ukraine does not reveal the concept of “cruelty” and relates it to the value category. That is its content is specified in the process of legal enforcement by assessing the particular circumstances of the proceedings. Let’s proceed to the analysis of doctrinal interpretation of the researched phenomenon. First, some scholars mistakenly equate violence and cruelty. The latter is not an act or omission, is not a way to commit a crime, it is the feature, an attribute of a character, person’s quality, condition or result of mental illness. It may be the quality indicator of the first. The latter approach to understanding of these categories on the etymology of words is correct. Therefore we emphasize: violence is a form of cruelty, its external expression. Cruelty is something inside the heart, and torments, torture, excruciation, mockery, humiliation are its external manifestation. Secondly, if violence often has a positive color, it is difficult to find situations, when human’s desire to cause suffering to others would be of a good color Cruelty in the criminal and legal perspective is situationally defined concept, but not thoroughly, so its content is specified in the process of legal enforcement by assessing the particular circumstances of the proceedings. Cruelty in criminological aspect is a negative attribute of a person’s character, who is indifferent to the suffering of others or in pursuit of their infliction. The information containing propaganda of cruelty is information or data of direct calls to cause or be indifferent to the suffering of others, deliberate demonstration in a naturalistic form: injection of horror, savoring torments, humiliation and suffering details; physiological reactions to injury or pain (martyr facial expressions, cries, groans, suffering, blood, agony, etc.); in actions of var- ious torture implements (knives, razors, axes, scissors, cutter, saws, chain saws, drills, etc.); mockery of the corpses, etc. However, not any information from the above stated is socially harmful, but only that one having deliberate or fostering goal of such a behavior. That is, it is necessary to evaluate a particular object in terms of a set of events and actions that determine the character of portrayed (the plot).

Проанализировано понятие «жестокость» в семантическом, уголовно-правовом и криминологическом аспектах. Определено, какие именно сведения или данные относятся к информации, содержащей пропаганду жестокости.
Олішевський, О. В. Визначення інформації, що містить пропаганду жорстокості: кримінально-правовий та кримінологічний аспекти / О. В. Олішевський // Вісник Кримінологічної асоціації України. - 2015. - № 2 (10). - С. 134-144.
Олішевський О. В. "Визначення інформації, що містить пропаганду жорстокості: кримінально-правовий та кримінологічний аспекти." Вісник Кримінологічної асоціації України 2 (2015): 134-144.
Keywords: Кримінологія. Criminology. Криминология; Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; жорстокість; особлива жорстокість; страждання; насильство; суспільно небезпечна інформація; cruelty; brutality; suffering; violence; socially dangerous information; жестокость; особая жестокость; страдания; насилие; общественно опасная информация